IMPLEMENTATION OF TGT MODEL ASSISTED BY QUIZIZZ TO ENHANCE STUDENTS' MATHEMATICS LEARNING MOTIVATION - Ditya Rizqi Karunia Wati; Siti Lailiyah; Maunah Setyawati (Universitas Muhammadiyah Metro, 2026)
Learning motivation is essential for students’ academic success, especially in mathematics, a subject commonly considered difficult. Classroom practices that are still teacher-centered may limit students’ participation and reduce interaction during learning activities. Therefore, an instructional strategy that encourages active involvement and creates a more engaging classroom atmosphere is needed. This study is intended to examine the improvement in students’ learning motivation by implementing the TGT model assisted with the support of Quizizz. The research applied a quantitative approach with a descriptive method utilizing a pre-experimental One-Group Pretest-Posttest design. The participants were 25 students drawn from grade VII F at MTs Negeri 4 Surabaya, selected by means of a random sampling technique. The data were obtained using a learning motivation survey instrument administered before and after the treatment, as well as observation sheets to assess the implementation process and students’ classroom activities. The findings reveal a rise in students’ learning motivation from 75% in the pretest to 90% in the posttest, while the implementation of learning and student activities reached 87.50%, categorized as very good. The results demonstrate that the TGT approach supported by Quizizz can foster a more interactive learning environment and contribute to improving students’ motivation within mathematics learning, especially in the topic of integers. Motivasi belajar memegang peranan penting dalam menunjang keberhasilan siswa, khususnya dalam pembelajaran matematika yang kerap dianggap sulit dan menantang. Kondisi pembelajaran yang masih berfokus pada guru cenderung menyebabkan keterlibatan siswa menjadi terbatas, sehingga interaksi dalam proses belajar belum berjalan secara optimal. Oleh sebab itu, dibutuhkan strategi pembelajaran yang mampu mengaktifkan peran siswa sekaligus menghadirkan suasana kelas yang lebih menarik. Penelitian ini bertujuan untuk menguraikan peningkatan motivasi belajar siswa melalui penerapan model TGT yang dipadukan dengan Quizizz. Penelitian ini menerapkan pendekatan kuantitatif dengan metode deskriptif serta menggunakan desain pra-eksperimental One-Group Pretest–Posttest. Subjek penelitian berjumlah 25 siswa kelas VII F MTs Negeri 4 Surabaya yang dipilih melalui teknik acak. Data dikumpulkan melalui angket motivasi belajar yang diberikan sebelum dan setelah pembelajaran berlangsung, serta lembar observasi yang digunakan untuk menilai keterlaksanaan pembelajaran dan aktivitas siswa selama proses berlangsung. Hasil penelitian memperlihatkan bahwa motivasi belajar siswa meningkat dari 75% pada kondisi awal menjadi 90% setelah penerapan model, sementara aktivitas siswa berada dalam kategori sangat baik. Temuan ini menunjukkan bahwa penggunaan model TGT berbantuan Quizizz dapat mendukung terciptanya pembelajaran yang lebih aktif dan interaktif, sehingga berdampak positif terhadap peningkatan motivasi belajar siswa pada materi bilangan bulat.